PENGUKURUAN KINERJA KEUANGAN DENGAN PENDEKATAN ECONOMIC VALUE ADDED (EVA) (STUDI KASUS PT TELEKOMUNIKASI INDONESIA TBK) - Sumatriani, Sumatriani; Nurdiah, Nurdiah (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2024)
This research was conducted at PT Telekomunikasi Indonesia Tbk, this research uses a quantitative type to calculate PT Telkom's EVA value. The data used are PT Telkom's financial reports, share price data, the composite stock price index (IHSG), and SBI interest rate data. This data is in the form of secondary data obtained from the Indonesian Stock Exchange, PT Telkom's Annual Report, and Bank Indonesia. These data were obtained using documentation techniques, while data analysis was carried out using quantitative data analysis using the Economic Value Added (EVA) approach. Based on the results of research and discussion, it is known that the EVA produced from 2015 to 2019 always has a positive value, namely EVA>0. This shows that the company value is in a positive condition, even though the resulting financial performance experiences fluctuating amounts which tend to decrease every year. This means that the company is able to create added economic value for both the company and investors in the form of additional wealth.